Function-oriented measurements and uncertainty evaluation of micro-gears for lifetime prognosis. Issue 1 (2017) - Haefner, Benjamin; Lanza, Gisela
Abstract: Micro-transmissions are used in manifold industrial applications, e.g. the medical industry. They consist of micro-gears with a module ≤200 μm showing large shape deviations compared to their size. Their main function is a proper operation over the required lifetime. Thus, for micro-gears lifetime prognosis dependent on their specific geometrical deviations is particularly important. For this purpose, a method is introduced to enable a suitable function-oriented evaluation of micro-gear measurements. High-precision 3D measurements are processed by finite element simulation to calculate realistic loads, and are correlated with experimental data of lifetime experiments. The uncertainty is evaluated according to GUM and Bayesian statistics.